Diseño de los parámetros técnicos para la convergencia de televisión analógica a televisión digital ISDB-Tb de TVS Canal 13 de la ciudad de riobamba. - Adriano Gallardo, Edwin Danilo (2013)
The following design is based primarily on the need for change from analogue to digital technology equipment company TVS channel 13 in the city of Riobamba, leading us on the parameters established by the Superintendency of Telecommunications, this change of technology to be beyond a mandatory change in a time bound, provides several benefits.